Assessing the impact of artificial intelligence integration on educational processes in higher education institutions of Ukraine and Kazakhstan - Bazyl, Olena; Abilova, Oryngul; Karpenko, Olena; Mierienkov, Hnat; Poliakova, Anastasiia (Sustainable Engineering and Innovation, 2025)
The study focuses on assessing the impact of artificial intelligence on educational processes in higher education institutions. It considers aspects of administrative task automation, personalization of learning, and ethical challenges. The topic’s relevance is driven by global trends in the digital transformation of education and the need to adapt systems to modern challenges. A descriptive approach was used, using secondary data from scientific publications, statistical reports, and analytical studies. The data were analyzed using statistical and correlation methods, allowing us to identify the key patterns of implementing artificial intelligence in higher education in Ukraine and Kazakhstan. Integration of artificial intelligence increases the efficiency of administrative processes by 40%, reducing the time spent on routine tasks. Personalized learning contributes to the growth of students’ academic performance by 7-30%. Using AI to monitor educational processes can reduce the risk of expulsions by up to 15%. At the same time, the risks of reduced social interaction and possible ethical issues, such as the opacity of algorithms and the risk of data leakage, have been identified. Artificial intelligence has significant potential for optimizing educational processes, provided ethical standards are met. Technological solutions must be combined with a socially oriented approach, particularly through integrating hybrid learning models. It is recommended that Ukraine use Kazakhstan’s experience in centralizing solutions, investing in analytical tools, and training teachers.